Implementasi Pembelajaran Pendidikan Agama Islam Berbasis Digital pada SD Muhammadiyah Bojonggede Bogor Kelas 3 Sampai Kelas 6 - Imam Tholkhah; Efrita Norman; Nadiah Nadiah (Jurnal Dirosah Islamiyah, 2023)
The development of science and technology (science and technology) is a challenge for Islamic education, especially when faced with the era of globalization which has been able to cover the distance and time between various countries in the exchange of information and knowledge, especially in the field of Islamic education. The purpose of this study is to describe and analyze (1) digital-based PAI learning planning, (2) digital media-based PAI learning implementation, (3) supporting and inhibiting factors in digital-based learning at SD Muhammadiyah Bojonggede. This study uses a qualitative approach. Data collection techniques through observation, interviews and documentation. Data were analyzed through data collection, data condensation, data presentation and drawing conclusions. Checking the validity of the data includes triangulation and membercheck techniques. The results of the study show that 1) learning planning that refers to the syllabus set by the government (dikbud) and PAI teachers are active in developing lesson plans, digital media-based learning planning is a learning design that utilizes technology as a learning medium with a teaching strategy that is centered on students, 2) SD Muhammadiyah Bojonggede has implemented various learning models including: (1) discovery learning; and (2) problem based learning and inquiring and implementation of teaching and learning activities in the classroom have used various digital-based learning media, 3) Supporting factors include the role of teachers who master the competence of managing digital-based learning which is the main key to digital success and inhibiting factors in the online learning process sometimes the signal is not good, the limitations of students who have android cellphones and the absence of quotas besides that are difficulties in dealing with differences in the characteristics of students Keywords: Digital-Based PAI Learning Implementation